The Malaysia-China Advanced TVET Mobility Programme (MyChat24) offers students a unique experience - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 2 July 2024 – The Malaysia-China Advanced TVET Mobility Programme (MyChat24) Phase 3 recently took place at Liuzhou Railway Vocational Technical College (LRVTC), China, lasting nine days.